Respuesta :
Answer: Choice A) -6
------------------------------------------------------------
------------------------------------------------------------
Work Shown:
f(x) = 17 - x^2
f(1) = 17 - (1)^2
f(1) = 17 - 1
f(1) = 16
--------------
f(x) = 17 - x^2
f(5) = 17 - (5)^2
f(5) = 17 - 25
f(5) = -8
--------------
m = (f(b) - f(a))/(b - a)
m = (f(5) - f(1))/(5 - 1)
m = (-8 - 16)/(5 - 1)
m = (-24)/(4)
m = -6
------------------------------------------------------------
------------------------------------------------------------
Work Shown:
f(x) = 17 - x^2
f(1) = 17 - (1)^2
f(1) = 17 - 1
f(1) = 16
--------------
f(x) = 17 - x^2
f(5) = 17 - (5)^2
f(5) = 17 - 25
f(5) = -8
--------------
m = (f(b) - f(a))/(b - a)
m = (f(5) - f(1))/(5 - 1)
m = (-8 - 16)/(5 - 1)
m = (-24)/(4)
m = -6
Answer:
Average rate of change is -6
Step-by-step explanation:
[tex]f(x)=17-x^2[/tex]
To find the average rate of change in f(x) over the interval [1, 5]
use formula Average = [tex]\frac{f(b)-f(a)}{b-a}[/tex]
Given interval is [1, 5] a=1, b=5
[tex]f(x)=17-x^2[/tex]
[tex]f(1)=17-1^2=16[/tex]
[tex]f(5)=17-5^2=-8[/tex]
Average = [tex]\frac{f(5)-f(1)}{5-1}[/tex]
=[tex]\frac{-8-16}{4}[/tex]
=[tex]\frac{-24}{4}=-6[/tex]
Average rate of change is -6